Sensory Analysis and Panelist Assessment on Paired of French Fries and Chili Sauce - Puspitasari, Armina Meikyo; Nurtama, Budi; Hunaefi, Dase (Universitas Djuanda, 2024)
Food pairing was the process of combining food or food and beverages to produce sensory characteristics. The consumption of snacks with commercial chili sauce as a supplement was widespread among consumers. Research on food pairing of commercial chili sauce with French fries was limited. The research aimed to describe and understand the sensory profile of chili sauce with its accompanying foods and identify changes in sensory attribute intensity when chili sauce was paired based on consumer perception. The methods used were Quantitative Descriptive Analysis and Rate All That Apply. The main ingredients were four commercial chili sauces and three commercial French fries. The sensory characteristics of chili sauce and French fries pairs were evaluated using QDA with trained panelists and RATA with consumer panelists. The results from the QDA method showed dominant characteristics such as potato flavor, crunchy texture, oily mouthfeel, sweet taste, and sour taste. According to PCA and spider web in QDA, it can be observed that the sample pairs with the highest intensity were sample pairs 47 and 87. Based on the RATA test results, According to PCA and spider web in RATA, it can be observed that the sample pair with the highest intensity was sample pair 65.